Penyusunan Instrumen Penilaian Pembelajaran Higher Order Thinking Skills Melalui Aplikasi ClassPoint - Sambas Ali Muhidin; Hady Siti Hadijah; Adman; Triesninda Pahlevi; Madziatul Churiyah; Marsofiyati (Universitas Negeri Surabaya, 2026)
Higher Order Thinking Skills (HOTS) are a crucial requirement in 21st-century learning, yet many teachers still struggle to develop appropriate assessment instruments. This community service activity aims to improve teachers' competency in designing HOTS assessment instruments based on the ClassPoint application, which allows for direct integration into interactive learning presentations. The methods used were participatory training and technical assistance to teachers. The results of the activity showed significant improvements in understanding HOTS concepts, the ability to develop analysis and synthesis items, and the utilization of ClassPoint features and direct evaluation. In conclusion, the use of ClassPoint as a medium for developing and implementing HOTS assessments has proven effective in supporting more meaningful and measurable learning. Keywords: ClassPoint, Assessment, Learning, HOTS